A glucose-utilizing strain, Cupriavidus euthrophus B-10646: growth kinetics, characterization and synthesis of multicomponent PHAs. - Tatiana Volova; Evgeniy Kiselev; Olga Vinogradova; Elena Nikolaeva; Anton Chistyakov; Aleksey Sukovatiy; Ekaterina Shishatskaya (PLoS ONE, 2014)
This study investigates kinetic and production parameters of a glucose-utilizing bacterial strain, C. eutrophus B-10646, and its ability to synthesize PHA terpolymers. Optimization of a number of parameters of bacterial culture (cell concentration in the inoculum, physiological activity of the inoculum, determined by the initial intracellular polymer content, and glucose concentration in the culture medium during cultivation) provided cell concentrations and PHA yields reaching 110 g/L and 80%, respectively, under two-stage batch culture conditions. Addition of precursor substrates (valerate, hexanoate, propionate, γ-butyrolactone) to the culture medium enabled synthesis of PHA terpolymers, P(3HB/3HV/4HB) and P(3HB/3HV/3HHx), with different composition and different molar fractions of 3HB, 3HV, 4HB, and 3HHx. Different types of PHA terpolymers synthesized by C. eutrophus B-10646 were used to prepare films, whose physicochemical and physical-mechanical properties were investigated. The properties of PHA terpolymers were significantly different from those of the P3HB homopolymer: they had much lower degrees of crystallinity and lower melting points and thermal decomposition temperatures, with the difference between these temperatures remaining practically unchanged. Films prepared from all PHA terpolymers had higher mechanical strength and elasticity than P3HB films. In spite of dissimilar surface structures, all films prepared from PHA terpolymers facilitated attachment and proliferation of mouse fibroblast NIH 3T3 cells more effectively than polystyrene and the highly crystalline P3HB.